Pupillometry as an objective measure of sustained attention in young and older listeners - Zhao, S; Bury, G; Milne, A; Chait, M (SAGE Publications, 2019)
The ability to sustain attention on a task-relevant sound source while avoiding distraction from concurrent sounds is fundamental to listening in crowded environments. We aimed to (a) devise an experimental paradigm with which this aspect of listening can be isolated and (b) evaluate the applicability of pupillometry as an objective measure of sustained attention in young and older populations. We designed a paradigm that continuously measured behavioral responses and pupillometry during 25-s trials. Stimuli contained a number of concurrent, spectrally distinct tone streams. On each trial, participants detected gaps in one of the streams while resisting distraction from the others. Behavior demonstrated increasing difficulty with time-on-task and with number/proximity of distractor streams. In young listeners (N = 20; aged 18 to 35 years), pupil diameter (on the group and individual level) was dynamically modulated by instantaneous task difficulty: Periods where behavioral performance revealed a strain on sustained attention were accompanied by increased pupil diameter. Only trials on which participants performed successfully were included in the pupillometry analysis so that the observed effects reflect task demands as opposed to failure to attend. In line with existing reports, we observed global changes to pupil dynamics in the older group (N = 19; aged 63 to 79 years) including decreased pupil diameter, limited dilation range, and reduced temporal variability. However, despite these changes, older listeners showed similar effects of attentive tracking to those observed in the young listeners. Overall, our results demonstrate that pupillometry can be a reliable and time-sensitive measure of attentive tracking over long durations in both young and (with caveats) older listeners.